1967
DOI: 10.1103/physrevlett.19.1334
|View full text |Cite
|
Sign up to set email alerts
|

Transport Properties at Critical Points: The Resistivity of Nickel

Abstract: The divergence of the temperature coefficient of resistivity of nickel at the Curie tem^ perature is emphasized. Application of the modified Ornstein-Zernike spin-pair correlation function is shown to yield results which cannot be made consistent with both resistivity and susceptibility results.The decrease in electrical resistance which is observed upon cooling a ferromagnet through the Curie temperature T c was discussed many years ago by Mott 1 and has been reviewed recently. 2 ' 3 The relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
2

Year Published

1975
1975
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 17 publications
(5 reference statements)
1
35
1
2
Order By: Relevance
“…Thus, ∆ρ will not only include the scattering from the 4f moments, but will also include scattering associated with the interaction between the 4f moments and itinerant electrons. is more conspicuous and must come from a different conduction electron scattering process (simple models of ρ(T ) due to magnetic scattering cannot explain this anomaly [35,36]). …”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Thus, ∆ρ will not only include the scattering from the 4f moments, but will also include scattering associated with the interaction between the 4f moments and itinerant electrons. is more conspicuous and must come from a different conduction electron scattering process (simple models of ρ(T ) due to magnetic scattering cannot explain this anomaly [35,36]). …”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…Sharp peaks in dρ xx, 0 /dT at T = T C have also been observed in ferromagnetic metals. 34,35 The critical behavior in case of metallic conductivity was explained long ago by Fisher and Langer, 36 who pointed out that short-range spin fluctuations are responsible for the singular behavior in dρ xx, 0 /dT at T = T C . The Fisher-Langer model, however, cannot be used to describe the peak in dρ xx, 0 /dT observed in this work, since ρ xx in n-HgCr 2 Se 4 is on the order of 10…”
Section: (C)mentioning
confidence: 99%
“…33,34,52 The Curie temperature T C can be determined by simply finding out which curve passes through the origin of the Arrott plot. According to Eq.…”
Section: Analysis Of Critical Exponents In Magnetizationmentioning
confidence: 99%
“…They have suggested that the magnetic resistivity is proportional to the spin-spin correlation, therefore it should behave as the magnetic susceptibility with a divergence at T c due to "long-range" fluctuations of the magnetization. Other authors [18][19][20] subsequently suggested that the shape of the resistivity results mainly from "short-range" correlation at T ≥ T c . Fisher and Langer [19] have shown in particular that the form of the resistivity cusp depends on the correlation range.…”
Section: Introductionmentioning
confidence: 99%